Influence of Parenting Style and Peer Acceptance on Early Childhood Interpersonal Skills - Nafis, Nilna Shifyana; Arbarini, Mintarsih; Diana, Diana (JURNAL PENDIDIKAN USIA DINI, 2025)
Parenting styles and peer acceptance significantly influence the development of interpersonal skills in young children. The support provided by both parents and peers plays a crucial role in helping children adapt and integrate into social environments during the preschool years. The aim of this study is to examine whether parental parenting styles and peer acceptance have an effect on the interpersonal skills of young children in Pati Regency. This research employs a quantitative approach with an ex-post facto design, specifically using a causal-comparative research model. The study's population includes children aged 4-6 years, their parents (either fathers or mothers), and teachers working at Raudlatul Athfal institutions in Pati Regency. The sample consists of 99 parents and 92 teachers, selected through cluster sampling. Data analysis was conducted using linear regression with SPSS for Windows. The findings indicate that both parental parenting styles and peer acceptance have a positive and significant impact on the interpersonal skills of young children in Pati Regency, with a coefficient of determination (R Square) value of 27%.